Konsep Pendidikan Akhlak Menurut Buya Hamka - Susanti, Salamah Eka (Lembaga Yasin AlSys, 2023)
This research aims to explore moral education from Buya Hamka's perspective and understand the methods used in character development. The method employed is qualitative, specifically library research. The findings suggest that education, according to Buya Hamka, involves inner behavior that can change; thus, when based on religious principles, it leads to good behavior, and vice versa. In the process of character development, parents and educators can utilize methods such as understanding, habituation (ta'widiyah), exemplification (uswatun hasanah), advice (mau’izhah al-hasanah), and storytelling (qishah).